Psychic Distance and Country Image in Exporter–Importer Relationships. Issue 3 (September 2016) - Durand, Aurélia; Turkina, Ekaterina; Robson, Matthew
Conflicting evidence on the issue of psychic distance (PD) in international business relationships has suggested the existence of misunderstood boundary conditions to its effect. This article argues that country image (CI) is a contingent factor to the effect of PD. Expectancy–value theory provides the theoretical foundations, and structural equation modeling analyses for a sample of 358 exporter–importer relationships in the global wine industry provide empirical support for this argument. Product-related CI mitigates the negative impact of PD on the relational exchange orientation (REO) between firms. Specifically, a high level of PD dampens REO when product-related CI is poor, whereas a strong product-related CI helps firms facing such PD conditions to build REO. People-related CI has an indirect effect on REO through product-related CI. This study helps explain the "paradox of distance" and offers a fresh perspective on how to handle the issue of PD when relevant.